DIPLOMASI KORPORAT SM ENTERTAINMENT DALAM MEMPERLUAS PASAR MELALUI NEW CULTURE TECHNOLOGY DI ASIA: Studi Kasus Indonesia dan Tiongkok - Nurul Nissa Salbia (2023)
The development of K-pop in Asia is increasingly spreading massively due to developments in technology and communication. SM Entertainment as a multinational company engaged in industrial culture uses corporate diplomacy to expand into foreign markets. This research specifically identifies SM Entertainment's efforts to expand its market to Indonesia and China. After analyzing using a qualitative method with a descriptive type of research, this study shows that through competitive intelligence, networking with external stakeholders, corporate reputation, and lobbying, SM Entertainment found a way to enter into the Indonesian and Chinese markets through market exploration facilitated by social media as a dissemination tool, live music concerts, joint ventures, localization strategies and omnidirectional marketing. This study found that there are similarities in the business strategies undertaken by SM Entertainment in entering the Indonesian and Chinese markets even though the flow of implementing these business strategies is different due to obstacles to K-pop acceptance. However, this business strategy was successfully implemented by SM Entertainment to enter and distribute K-pop in the markets of the two countries.